Augmented blood pressure measurement through the estimation of physiological blood pressure variability - Soueidan, Karen (University of Ottawa (Canada), 2010)
Current noninvasive blood pressure (BP) measurement methods estimate the systolic and diastolic blood pressure (SBP and DBP) at two random instants in time. The BP variability and its serious consequences on the measurement are not recognized by most physicians. The standard for automated BP devices sets a maximum allowable system error of +/- 5 mmHg, even though natural BP variability often exceeds these limits. This thesis characterizes the variability of SBP and DBP and proposes a new approach to augment the conventional noninvasive measurement using simultaneous recordings of the oscillometric and continuous arterial pulse waveforms by providing: 1) The mean SBP (or DBP) over the measurement interval, 2) Their respective standard deviations, and 3) An indicator as to whether or not the oscillometric reading is an outlier. Recordings with healthy subjects showed that the approach has prominent potential and does not suffer from bias relative to the conventional method.
Keywords: Engineering, Biomedical.; Biology, Physiology.